2001
DOI: 10.1017/s0790966700006595
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of Irish trainees to their training and its supervision: a five-year follow up study

Abstract: Objectives: To assess the current attitudes of Irish psychiatric trainees to their training and to determine whether problems identified five years ago have improved.Method: A postal questionnaire was circulated to all identified psychiatric trainees in the eastern region of Ireland over a six-month period in 2000.Results: 153 (62%) trainees responded to the study, and 81% described their training as ‘adequate’ or better. Significant demographic changes over the last five years are recorded. Satisfactory induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…The literature underscores that such events have a considerable impact on trainees. 4,[13][14][15] Relationships in this area appear to be complex; our study found a small association between duress and stress, that only threats of legal action were associated with higher stress and a lack of association of these with satisfaction.…”
Section: Number Of Traineescontrasting
confidence: 63%
“…The literature underscores that such events have a considerable impact on trainees. 4,[13][14][15] Relationships in this area appear to be complex; our study found a small association between duress and stress, that only threats of legal action were associated with higher stress and a lack of association of these with satisfaction.…”
Section: Number Of Traineescontrasting
confidence: 63%
“…Meagher et al (1997) reported that as much as 27% of trainees in Ireland had experienced violence at work, but our findings are more in keeping with the study of O'Mahony & Corvin (2001) which also found 16% trainees to be affected. O'Sullivan & Meagher (1998) found that 39% of all psychiatrists had been physically assaulted, with trainees at higher risk.…”
Section: Discussionsupporting
confidence: 89%
“…A further 85% reported that they received breakaway training or engaged in a similar course. This compares with a rate of less than a third of trainees as reported by O'Mahony & Corvin in 2001(O'Mahony & Corvin, 2001, which suggests that it is only in recent years that there has been a sea change in availability of such courses.…”
Section: Discussionmentioning
confidence: 65%
“…A follow-up study showed that 16% of trainees had experienced violence at work, but more than two-thirds had no training in 'breakaway' techniques, only 25% were aware of a critical incident debriefing service in their area and most were dissatisfied with the induction training provided by their employers. 4 Younger psychiatrists were at an increased risk of assault compared with older psychiatrists. 5 In 2006, a national survey was conducted by our working group which examined the experience of trainees in psychiatry in the Republic of Ireland.…”
Section: Irish Studiesmentioning
confidence: 99%